ОСОБЕННОСТИ ПЕТРОФИЗИЧЕСКИХ СВОЙСТВ ДОЛОМИТОВ - Митрофанов В.П. (My University, 2002)
Рассмотрены особенности доломитизации и сульфатизации пород, влияния их на коллекторские свойства. Для различных типов доломитов проведены зависимости соотношения пористости, проницаемости, поровых каналов, эффективной пористости.

Peculiarities of rocks dolomitization and sulphatization are examined in the article, their influence on reservoir properties. For different types of dolomites it is given concrete dependence of ratio of porosity, permeability, pore canals, effective porosity.
Keywords: 552.5:553.98.048